Recent Advancements in Gallic Acid-Based Drug Delivery: Applications, Clinical Trials, and Future Directions - Ranjit K. Harwansh; Rohitas Deshmukh; Vijay Pratap Shukla; Dignesh Khunt; Bhupendra Gopalbhai Prajapati; Summya Rashid; Nemat Ali; Gehan M. Elossaily; Vijendra Kumar Suryawanshi; Arun Kumar (MDPI AG, 2024)
Gallic acid (GA) is a well-known herbal bioactive compound found in many herbs and foods like tea, wine, cashew nuts, hazelnuts, walnuts, plums, grapes, mangoes, blackberries, blueberries, and strawberries. GA has been reported for several pharmacological activities, such as antioxidant, inflammatory, antineoplastic, antimicrobial, etc. Apart from its incredible therapeutic benefits, it has been associated with low permeability and bioavailability issues, limiting their efficacy. GA belongs to BCS (Biopharmaceutics classification system) class III (high solubility and low probability). In this context, novel drug delivery approaches played a vital role in resolving these GA issues. Nanocarrier systems help improve drug moiety's physical and chemical stability by encapsulating them into a lipidic or polymeric matrix or core system. In this regard, researchers have developed a wide range of nanocarrier systems for GA, including liposomes, transfersomes, niosomes, dendrimers, phytosomes, micelles, nanoemulsions, metallic nanoparticles, solid lipid nanoparticles (SLNs), nanoparticles, nanostructured lipid carriers, polymer conjugates, etc. In the present review, different search engines like Scopus, PubMed, ScienceDirect, and Google Scholar have been referred to for acquiring recent information on the theme of the work. Therefore, this review paper aims to emphasize several novel drug delivery systems, patents, and clinical updates of GA.